Displacing the Family: Union Army Pensions and Elderly Living Arrangements - Costa, Dora L. (Journal of Political Economy, 1997)
I investigate the factors that fostered the rise in separate living quarters for the aged prior to Social Security by estimating the income effect of the first major pension program in the United States, that covering Union Army veterans. I find that income substantially increased demand for separate living arrangements, suggesting that prior to 1940 rising incomes were the most important factor enabling the elderly to live alone. Comparisons with recent studies imply that income no longer plays as large a role, perhaps because income levels are now higher and independent living is both less expensive and more attractive.